Remote teaching of Ume Sámi to young learners in Sweden - Lindelöf Sara; Toropainen Outi (United Kingdom, 2025)
This article is based on a qualitative case study of remote teaching in the endangered, indigenous language Ume Sámi. The purpose of the study is to support the revitalisation of the endangered Ume Sámi language in educational settings. Further, the aims for the study is to enhance knowledge of teaching this language. Through teacher interviews and lesson observations, the study focuses on teacher experiences in the remote teaching of young learners. The verbatim-transcribed data was analysed through a data-driven thematic analysis. The results show that remote education is necessary for teaching Ume Sámi due to the geographical distribution of the Sámi people. The challenges of teaching through remote education originate outside the digital Ume Sámi classroom. Challenges identified in this study comprise teaching time, scheduling across different schools, shortage of educational material in the Ume Sámi language and lack of commitment from the young learners’ regular school. Moreover, teachers perceive that communicating Sámi culture beyond language is challenging due to a shortage of resources. The cultural aspects are crucial, especially when pupils live outside Sápmi, the core geographical area of the Sámi people. Teachers expressed a desire for conventional Swedish schools to carry their responsibility and teach about Sápmi and the Sámi people to all pupils in Sweden.